ПИСАТЕЛЬ И ИЗДАТЕЛЬ: КОНСТАНТИН ЛЕОНТЬЕВ О МИХАИЛЕ КАТКОВЕ (К ПРОБЛЕМЕ ВЗАИМООТНОШЕНИЙ) - Łucewicz, Ludmiła (Przegląd Rusycystyczny, 2016)
WRITER AND PU BLIS HER : KONSTANTIN LE ONTE V ABOUT MI KHAIL KAT KOV (TO THE PR OBLEM OF MUTUAL RELATI ONS ) S u m m a r y The author in her article marked that for description of mutual relations of writer and publisher there is not equivalent information, i.e. there are numerous judgements, autobiographic compositions, special article of Leontev relatively Кatkov, but there is nothing of the kind outside of Кatkov. A writer, lining up the version of mutual relations with a publisher in 70th, does an accent especially on a negative. As a result Katkov appears a man authoritarian, mercenary, proud, apathetic, lacking in initiative in the judgements. At the same time the facts marked a writer on the way talk and about other: not only about the real material help of Кatkov, but also about his participating in spiritual development of junior contemporary. Attention in the article is concentrated on two plans of confessional texts of Leontev: on a correlation of the subjective descriptions given by a writer to the publisher and objective facts of positive participation of publisher in the fate of writer.